LEARNING TRIGONOMETRIC FUNCTIONS WITH GEOMETER'S SKETCHPAD FOR IMPROVING LEARNING RESULTS STUDENT MATHEMATICS IN CLASS X SMA/MA - Hafriani Hafriani Hafriani; Nadia Husna Turrizky; Kamarullah Kamarullah Kamarullah (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2023)
This research is motivated by the low learning outcomes of students' mathematics, especially the material on trigonometric functions due to abstract mathematics and teachers who must have skills in the field of technology because they can help explain the learning material in totality. The aims of this study are (1) to determine student learning outcomes using the application of Geometer's Sketchpad software in learning material on trigonometric functions and (2) to determine the comparison of student learning outcomes with the help of Geometer's Sketchpad software can be better than student learning outcomes without Geometer's Sketchpad in class. X SMA/MA. This research is a quantitative research with a pretest-posttest control design. Sampling in this study was taken by total sampling.learning trigonometric functions in class with the help of Geometer's Sketchpad. The teacher uses infocus and guides students in the process of drawing graphs and students are also able to explain the amplitude, period, maximum value and minimum value and are able to write equations that match the graph. It is stated that the application of Geometer's Sketchpad software in learning trigonometric function material is better than learning trigonometric functions by not using software. It is proven by the posttest value which is significantly increased from the pretest value of the experimental class(2) The results of the experimental and control class posttest data that have been carried out and obtained> that is 5.87 > 1.68. Then it can be concluded that it is rejected and thus accepted, so that the learning outcomes of trigonometric function material with the help of Geometer's Sketchpad can be better than student learning outcomes without Geometer's Sketchpad in class X SMA/MA.